Factores socioafectivos asociados al desempeño del modelaje webcam en una mujer del municipio de Cartago Valle - Ángela Patricia, Fernández (Universidad Antonio Nariño, 2023)
In this research, an observation of how socio-affective factors can affect the performance in webcam modeling is carried out, this through what the participant relates. The methodology is qualitative, the design is a case study, therefore, the information is obtained through an instrument according to the research; a semi-structured interview applied to a female participant of 25 years of age from the city of Cartago Valle, who relates her experience in response to the questions raised in this research.